Los estilos educativos parentales y la relación con el locus de control de los estudiantes de noveno y décimo grado, de la escuela de educación básica Amauta, 2020-2021. - Abad Torres, Andrea de Fátima (2021)
A research whose purpose was to introduce a little explored study related to parental educational styles and Locus of Control, called: "Parental educational styles and the relationship with the locus of control of ninth and tenth grade students of the basic education school Amauta, 2020- 2021. "In order to have a guiding thread for the research, the general objective was: To analyze the parental educational styles and their relationship with the locus of control (style of action of each person, their beliefs) of the ninth and tenth grade students. The methodology that guided the research process was of quantitative approach, non-experimental design, cross-sectional and correlational level. As a technique, the EMBU 89 test (children) and the Rotter Locus of Control Questionnaire were applied to the research sample, aged between 12 and 14 years. The results obtained were that 81.81% of the students perceive their parents as having a democratic educational style, due to the high level of understanding and support, and medium level of pressure towards achievement. In addition, low levels of Punishment were evidenced. However, a mixed educational style (democratic, authoritarian and permissive) was present in 18.18% due to the dimensions of Overprotection and Rejection at medium levels. The predominant type of locus of control was the internal locus of control with 54.54% versus the external locus of control with 45.45%. These data were processed with the Chi-square test, obtaining a P-value = 0.087, from which it is concluded that there is no significant relationship between the variables, educational styles and locus of control. It is recommended that the director of the institution implement the psychoeducational proposal to make the type of locus of control conscious through exercises of the Stoic Philosophy.